Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
File size: 42,988 Bytes
4365a98 fc5e983 4365a98 |
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313 314 315 316 317 318 319 320 321 322 323 324 325 326 327 328 329 330 331 332 333 334 335 336 337 338 339 340 341 342 343 344 345 346 347 348 349 350 351 352 353 354 355 356 357 358 359 360 361 362 363 364 365 366 367 368 369 370 371 372 373 374 375 376 377 378 379 380 381 382 383 384 385 386 387 388 389 390 391 392 393 394 395 396 397 398 399 400 401 402 403 404 405 406 407 408 409 410 411 412 413 414 415 416 417 418 419 420 421 422 423 424 425 426 427 428 429 430 431 432 433 434 435 436 437 438 439 440 441 442 443 444 445 446 447 448 449 450 451 452 453 454 455 456 457 458 459 460 461 462 463 464 465 466 467 468 469 470 471 472 473 474 475 476 477 478 479 480 481 482 483 484 485 486 487 488 489 490 491 492 493 494 495 496 497 498 499 500 501 502 503 504 505 506 507 508 509 510 511 512 513 514 515 516 517 518 519 520 521 522 523 524 525 526 527 528 529 530 531 532 533 534 535 536 537 538 539 540 541 542 543 544 545 546 547 548 549 550 551 552 553 554 555 556 557 558 559 560 561 562 563 564 565 566 567 568 569 570 571 572 573 574 575 576 577 578 579 580 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 618 619 620 621 622 623 624 625 626 627 628 629 630 631 632 633 634 635 636 637 638 639 640 641 642 643 644 645 646 647 648 649 650 651 652 653 654 655 656 657 658 659 660 661 662 663 664 665 666 667 668 669 670 671 672 673 674 675 676 677 678 679 680 681 682 683 684 685 686 687 688 689 690 691 692 693 694 695 696 697 698 699 700 701 702 703 704 705 706 707 708 709 710 711 712 713 714 715 716 717 718 719 720 721 722 723 724 725 726 727 728 729 730 731 732 733 734 735 736 737 738 739 740 741 742 743 744 745 746 747 748 749 750 751 752 753 754 755 756 757 758 759 760 761 762 763 764 765 766 767 768 769 770 771 772 773 774 775 776 777 778 779 780 781 782 783 784 785 786 787 788 789 790 791 792 793 794 795 796 797 798 799 800 801 802 803 804 805 806 807 808 809 810 811 812 813 814 815 816 817 818 819 820 821 822 823 824 825 826 827 828 829 830 831 832 833 834 835 836 837 838 839 840 841 842 843 844 845 846 847 848 849 850 851 852 853 854 855 856 857 858 859 860 861 862 863 864 865 866 867 868 869 870 871 872 873 874 875 876 877 878 879 880 881 882 883 884 885 886 887 888 889 890 891 892 893 894 895 896 897 898 899 900 901 902 903 904 905 906 907 908 909 910 911 912 913 914 915 916 917 918 919 920 921 922 923 924 925 926 927 928 929 930 931 932 933 934 935 936 937 938 939 940 941 942 943 944 945 946 947 948 949 950 951 952 953 954 955 956 957 958 959 960 961 962 963 964 965 966 967 968 969 970 971 972 973 974 975 976 977 978 979 980 981 982 983 984 985 986 987 988 989 990 991 992 993 994 995 996 997 998 999 1000 1001 1002 1003 1004 1005 1006 1007 1008 1009 1010 1011 1012 1013 1014 1015 1016 1017 1018 1019 1020 1021 1022 1023 1024 1025 1026 1027 1028 1029 1030 1031 1032 1033 1034 1035 1036 1037 1038 1039 1040 1041 1042 1043 1044 1045 1046 1047 1048 1049 1050 1051 1052 1053 1054 1055 1056 1057 1058 |
/-
Copyright (c) 2020 Zhangir Azerbayev. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Eric Wieser, Zhangir Azerbayev
-/
import group_theory.group_action.quotient
import group_theory.perm.sign
import group_theory.perm.subgroup
import linear_algebra.linear_independent
import linear_algebra.multilinear.basis
import linear_algebra.multilinear.tensor_product
import logic.equiv.fin
/-!
# Alternating Maps
We construct the bundled function `alternating_map`, which extends `multilinear_map` with all the
arguments of the same type.
## Main definitions
* `alternating_map R M N ι` is the space of `R`-linear alternating maps from `ι → M` to `N`.
* `f.map_eq_zero_of_eq` expresses that `f` is zero when two inputs are equal.
* `f.map_swap` expresses that `f` is negated when two inputs are swapped.
* `f.map_perm` expresses how `f` varies by a sign change under a permutation of its inputs.
* An `add_comm_monoid`, `add_comm_group`, and `module` structure over `alternating_map`s that
matches the definitions over `multilinear_map`s.
* `multilinear_map.dom_dom_congr`, for permutating the elements within a family.
* `multilinear_map.alternatization`, which makes an alternating map out of a non-alternating one.
* `alternating_map.dom_coprod`, which behaves as a product between two alternating maps.
* `alternating_map.curry_left`, for binding the leftmost argument of an alternating map indexed
by `fin n.succ`.
## Implementation notes
`alternating_map` is defined in terms of `map_eq_zero_of_eq`, as this is easier to work with than
using `map_swap` as a definition, and does not require `has_neg N`.
`alternating_map`s are provided with a coercion to `multilinear_map`, along with a set of
`norm_cast` lemmas that act on the algebraic structure:
* `alternating_map.coe_add`
* `alternating_map.coe_zero`
* `alternating_map.coe_sub`
* `alternating_map.coe_neg`
* `alternating_map.coe_smul`
-/
-- semiring / add_comm_monoid
variables {R : Type*} [semiring R]
variables {M : Type*} [add_comm_monoid M] [module R M]
variables {N : Type*} [add_comm_monoid N] [module R N]
-- semiring / add_comm_group
variables {M' : Type*} [add_comm_group M'] [module R M']
variables {N' : Type*} [add_comm_group N'] [module R N']
variables {ι ι' ι'' : Type*} [decidable_eq ι] [decidable_eq ι'] [decidable_eq ι'']
set_option old_structure_cmd true
section
variables (R M N ι)
/--
An alternating map is a multilinear map that vanishes when two of its arguments are equal.
-/
structure alternating_map extends multilinear_map R (λ i : ι, M) N :=
(map_eq_zero_of_eq' : ∀ (v : ι → M) (i j : ι) (h : v i = v j) (hij : i ≠ j), to_fun v = 0)
end
/-- The multilinear map associated to an alternating map -/
add_decl_doc alternating_map.to_multilinear_map
namespace alternating_map
variables (f f' : alternating_map R M N ι)
variables (g g₂ : alternating_map R M N' ι)
variables (g' : alternating_map R M' N' ι)
variables (v : ι → M) (v' : ι → M')
open function
/-! Basic coercion simp lemmas, largely copied from `ring_hom` and `multilinear_map` -/
section coercions
instance : has_coe_to_fun (alternating_map R M N ι) (λ _, (ι → M) → N) := ⟨λ x, x.to_fun⟩
initialize_simps_projections alternating_map (to_fun → apply)
@[simp] lemma to_fun_eq_coe : f.to_fun = f := rfl
@[simp] lemma coe_mk (f : (ι → M) → N) (h₁ h₂ h₃) : ⇑(⟨f, h₁, h₂, h₃⟩ :
alternating_map R M N ι) = f := rfl
theorem congr_fun {f g : alternating_map R M N ι} (h : f = g) (x : ι → M) : f x = g x :=
congr_arg (λ h : alternating_map R M N ι, h x) h
theorem congr_arg (f : alternating_map R M N ι) {x y : ι → M} (h : x = y) : f x = f y :=
congr_arg (λ x : ι → M, f x) h
theorem coe_injective : injective (coe_fn : alternating_map R M N ι → ((ι → M) → N)) :=
λ f g h, by { cases f, cases g, cases h, refl }
@[simp, norm_cast] theorem coe_inj {f g : alternating_map R M N ι} :
(f : (ι → M) → N) = g ↔ f = g :=
coe_injective.eq_iff
@[ext] theorem ext {f f' : alternating_map R M N ι} (H : ∀ x, f x = f' x) : f = f' :=
coe_injective (funext H)
theorem ext_iff {f g : alternating_map R M N ι} : f = g ↔ ∀ x, f x = g x :=
⟨λ h x, h ▸ rfl, λ h, ext h⟩
instance : has_coe (alternating_map R M N ι) (multilinear_map R (λ i : ι, M) N) :=
⟨λ x, x.to_multilinear_map⟩
@[simp, norm_cast] lemma coe_multilinear_map : ⇑(f : multilinear_map R (λ i : ι, M) N) = f := rfl
lemma coe_multilinear_map_injective :
function.injective (coe : alternating_map R M N ι → multilinear_map R (λ i : ι, M) N) :=
λ x y h, ext $ multilinear_map.congr_fun h
@[simp] lemma to_multilinear_map_eq_coe : f.to_multilinear_map = f := rfl
@[simp] lemma coe_multilinear_map_mk (f : (ι → M) → N) (h₁ h₂ h₃) :
((⟨f, h₁, h₂, h₃⟩ : alternating_map R M N ι) : multilinear_map R (λ i : ι, M) N) = ⟨f, h₁, h₂⟩ :=
rfl
end coercions
/-!
### Simp-normal forms of the structure fields
These are expressed in terms of `⇑f` instead of `f.to_fun`.
-/
@[simp] lemma map_add (i : ι) (x y : M) :
f (update v i (x + y)) = f (update v i x) + f (update v i y) :=
f.to_multilinear_map.map_add' v i x y
@[simp] lemma map_sub (i : ι) (x y : M') :
g' (update v' i (x - y)) = g' (update v' i x) - g' (update v' i y) :=
g'.to_multilinear_map.map_sub v' i x y
@[simp] lemma map_neg (i : ι) (x : M') :
g' (update v' i (-x)) = -g' (update v' i x) :=
g'.to_multilinear_map.map_neg v' i x
@[simp] lemma map_smul (i : ι) (r : R) (x : M) :
f (update v i (r • x)) = r • f (update v i x) :=
f.to_multilinear_map.map_smul' v i r x
@[simp] lemma map_eq_zero_of_eq (v : ι → M) {i j : ι} (h : v i = v j) (hij : i ≠ j) :
f v = 0 :=
f.map_eq_zero_of_eq' v i j h hij
lemma map_coord_zero {m : ι → M} (i : ι) (h : m i = 0) : f m = 0 :=
f.to_multilinear_map.map_coord_zero i h
@[simp] lemma map_update_zero (m : ι → M) (i : ι) : f (update m i 0) = 0 :=
f.to_multilinear_map.map_update_zero m i
@[simp] lemma map_zero [nonempty ι] : f 0 = 0 :=
f.to_multilinear_map.map_zero
lemma map_eq_zero_of_not_injective (v : ι → M) (hv : ¬function.injective v) : f v = 0 :=
begin
rw function.injective at hv,
push_neg at hv,
rcases hv with ⟨i₁, i₂, heq, hne⟩,
exact f.map_eq_zero_of_eq v heq hne
end
/-!
### Algebraic structure inherited from `multilinear_map`
`alternating_map` carries the same `add_comm_monoid`, `add_comm_group`, and `module` structure
as `multilinear_map`
-/
section has_smul
variables {S : Type*} [monoid S] [distrib_mul_action S N] [smul_comm_class R S N]
instance : has_smul S (alternating_map R M N ι) :=
⟨λ c f,
{ map_eq_zero_of_eq' := λ v i j h hij, by simp [f.map_eq_zero_of_eq v h hij],
..((c • f : multilinear_map R (λ i : ι, M) N)) }⟩
@[simp] lemma smul_apply (c : S) (m : ι → M) :
(c • f) m = c • f m := rfl
@[norm_cast] lemma coe_smul (c : S):
((c • f : alternating_map R M N ι) : multilinear_map R (λ i : ι, M) N) = c • f := rfl
lemma coe_fn_smul (c : S) (f : alternating_map R M N ι) : ⇑(c • f) = c • f :=
rfl
instance [distrib_mul_action Sᵐᵒᵖ N] [is_central_scalar S N] :
is_central_scalar S (alternating_map R M N ι) :=
⟨λ c f, ext $ λ x, op_smul_eq_smul _ _⟩
end has_smul
instance : has_add (alternating_map R M N ι) :=
⟨λ a b,
{ map_eq_zero_of_eq' :=
λ v i j h hij, by simp [a.map_eq_zero_of_eq v h hij, b.map_eq_zero_of_eq v h hij],
..(a + b : multilinear_map R (λ i : ι, M) N)}⟩
@[simp] lemma add_apply : (f + f') v = f v + f' v := rfl
@[norm_cast] lemma coe_add : (↑(f + f') : multilinear_map R (λ i : ι, M) N) = f + f' := rfl
instance : has_zero (alternating_map R M N ι) :=
⟨{map_eq_zero_of_eq' := λ v i j h hij, by simp,
..(0 : multilinear_map R (λ i : ι, M) N)}⟩
@[simp] lemma zero_apply : (0 : alternating_map R M N ι) v = 0 := rfl
@[norm_cast] lemma coe_zero :
((0 : alternating_map R M N ι) : multilinear_map R (λ i : ι, M) N) = 0 := rfl
instance : inhabited (alternating_map R M N ι) := ⟨0⟩
instance : add_comm_monoid (alternating_map R M N ι) :=
coe_injective.add_comm_monoid _ rfl (λ _ _, rfl) (λ _ _, coe_fn_smul _ _)
instance : has_neg (alternating_map R M N' ι) :=
⟨λ f,
{ map_eq_zero_of_eq' := λ v i j h hij, by simp [f.map_eq_zero_of_eq v h hij],
..(-(f : multilinear_map R (λ i : ι, M) N')) }⟩
@[simp] lemma neg_apply (m : ι → M) : (-g) m = -(g m) := rfl
@[norm_cast] lemma coe_neg :
((-g : alternating_map R M N' ι) : multilinear_map R (λ i : ι, M) N') = -g := rfl
instance : has_sub (alternating_map R M N' ι) :=
⟨λ f g,
{ map_eq_zero_of_eq' :=
λ v i j h hij, by simp [f.map_eq_zero_of_eq v h hij, g.map_eq_zero_of_eq v h hij],
..(f - g : multilinear_map R (λ i : ι, M) N') }⟩
@[simp] lemma sub_apply (m : ι → M) : (g - g₂) m = g m - g₂ m := rfl
@[norm_cast] lemma coe_sub : (↑(g - g₂) : multilinear_map R (λ i : ι, M) N') = g - g₂ := rfl
instance : add_comm_group (alternating_map R M N' ι) :=
coe_injective.add_comm_group _ rfl (λ _ _, rfl) (λ _, rfl) (λ _ _, rfl)
(λ _ _, coe_fn_smul _ _) (λ _ _, coe_fn_smul _ _)
section distrib_mul_action
variables {S : Type*} [monoid S] [distrib_mul_action S N] [smul_comm_class R S N]
instance : distrib_mul_action S (alternating_map R M N ι) :=
{ one_smul := λ f, ext $ λ x, one_smul _ _,
mul_smul := λ c₁ c₂ f, ext $ λ x, mul_smul _ _ _,
smul_zero := λ r, ext $ λ x, smul_zero _,
smul_add := λ r f₁ f₂, ext $ λ x, smul_add _ _ _ }
end distrib_mul_action
section module
variables {S : Type*} [semiring S] [module S N] [smul_comm_class R S N]
/-- The space of multilinear maps over an algebra over `R` is a module over `R`, for the pointwise
addition and scalar multiplication. -/
instance : module S (alternating_map R M N ι) :=
{ add_smul := λ r₁ r₂ f, ext $ λ x, add_smul _ _ _,
zero_smul := λ f, ext $ λ x, zero_smul _ _ }
instance [no_zero_smul_divisors S N] : no_zero_smul_divisors S (alternating_map R M N ι) :=
coe_injective.no_zero_smul_divisors _ rfl coe_fn_smul
end module
section
variables (R M)
/-- The evaluation map from `ι → M` to `M` at a given `i` is alternating when `ι` is subsingleton.
-/
@[simps]
def of_subsingleton [subsingleton ι] (i : ι) : alternating_map R M M ι :=
{ to_fun := function.eval i,
map_eq_zero_of_eq' := λ v i j hv hij, (hij $ subsingleton.elim _ _).elim,
..multilinear_map.of_subsingleton R M i }
/-- The constant map is alternating when `ι` is empty. -/
@[simps {fully_applied := ff}]
def const_of_is_empty [is_empty ι] (m : N) : alternating_map R M N ι :=
{ to_fun := function.const _ m,
map_eq_zero_of_eq' := λ v, is_empty_elim,
..multilinear_map.const_of_is_empty R m }
end
/-- Restrict the codomain of an alternating map to a submodule. -/
@[simps]
def cod_restrict (f : alternating_map R M N ι) (p : submodule R N) (h : ∀ v, f v ∈ p) :
alternating_map R M p ι :=
{ to_fun := λ v, ⟨f v, h v⟩,
map_eq_zero_of_eq' := λ v i j hv hij, subtype.ext $ map_eq_zero_of_eq _ _ hv hij,
..f.to_multilinear_map.cod_restrict p h }
end alternating_map
/-!
### Composition with linear maps
-/
namespace linear_map
variables {N₂ : Type*} [add_comm_monoid N₂] [module R N₂]
/-- Composing a alternating map with a linear map on the left gives again an alternating map. -/
def comp_alternating_map (g : N →ₗ[R] N₂) : alternating_map R M N ι →+ alternating_map R M N₂ ι :=
{ to_fun := λ f,
{ map_eq_zero_of_eq' := λ v i j h hij, by simp [f.map_eq_zero_of_eq v h hij],
..(g.comp_multilinear_map (f : multilinear_map R (λ _ : ι, M) N)) },
map_zero' := by { ext, simp },
map_add' := λ a b, by { ext, simp } }
@[simp] lemma coe_comp_alternating_map (g : N →ₗ[R] N₂) (f : alternating_map R M N ι) :
⇑(g.comp_alternating_map f) = g ∘ f := rfl
@[simp]
lemma comp_alternating_map_apply (g : N →ₗ[R] N₂) (f : alternating_map R M N ι) (m : ι → M) :
g.comp_alternating_map f m = g (f m) := rfl
@[simp]
lemma subtype_comp_alternating_map_cod_restrict (f : alternating_map R M N ι) (p : submodule R N)
(h) :
p.subtype.comp_alternating_map (f.cod_restrict p h) = f :=
alternating_map.ext $ λ v, rfl
@[simp]
lemma comp_alternating_map_cod_restrict (g : N →ₗ[R] N₂) (f : alternating_map R M N ι)
(p : submodule R N₂) (h) :
(g.cod_restrict p h).comp_alternating_map f =
(g.comp_alternating_map f).cod_restrict p (λ v, h (f v)):=
alternating_map.ext $ λ v, rfl
end linear_map
namespace alternating_map
variables {M₂ : Type*} [add_comm_monoid M₂] [module R M₂]
variables {M₃ : Type*} [add_comm_monoid M₃] [module R M₃]
/-- Composing a alternating map with the same linear map on each argument gives again an
alternating map. -/
def comp_linear_map (f : alternating_map R M N ι) (g : M₂ →ₗ[R] M) : alternating_map R M₂ N ι :=
{ map_eq_zero_of_eq' := λ v i j h hij, f.map_eq_zero_of_eq _ (linear_map.congr_arg h) hij,
.. (f : multilinear_map R (λ _ : ι, M) N).comp_linear_map (λ _, g) }
lemma coe_comp_linear_map (f : alternating_map R M N ι) (g : M₂ →ₗ[R] M) :
⇑(f.comp_linear_map g) = f ∘ ((∘) g) := rfl
@[simp] lemma comp_linear_map_apply (f : alternating_map R M N ι) (g : M₂ →ₗ[R] M) (v : ι → M₂) :
f.comp_linear_map g v = f (λ i, g (v i)) := rfl
/-- Composing an alternating map twice with the same linear map in each argument is
the same as composing with their composition. -/
lemma comp_linear_map_assoc (f : alternating_map R M N ι) (g₁ : M₂ →ₗ[R] M) (g₂ : M₃ →ₗ[R] M₂) :
(f.comp_linear_map g₁).comp_linear_map g₂ = f.comp_linear_map (g₁ ∘ₗ g₂) :=
rfl
@[simp] lemma zero_comp_linear_map (g : M₂ →ₗ[R] M) :
(0 : alternating_map R M N ι).comp_linear_map g = 0 :=
by { ext, simp only [comp_linear_map_apply, zero_apply] }
@[simp] lemma add_comp_linear_map (f₁ f₂ : alternating_map R M N ι) (g : M₂ →ₗ[R] M) :
(f₁ + f₂).comp_linear_map g = f₁.comp_linear_map g + f₂.comp_linear_map g :=
by { ext, simp only [comp_linear_map_apply, add_apply] }
@[simp] lemma comp_linear_map_zero [nonempty ι] (f : alternating_map R M N ι) :
f.comp_linear_map (0 : M₂ →ₗ[R] M) = 0 :=
begin
ext,
simp_rw [comp_linear_map_apply, linear_map.zero_apply, ←pi.zero_def, map_zero, zero_apply],
end
/-- Composing an alternating map with the identity linear map in each argument. -/
@[simp] lemma comp_linear_map_id (f : alternating_map R M N ι) :
f.comp_linear_map linear_map.id = f :=
ext $ λ _, rfl
/-- Composing with a surjective linear map is injective. -/
lemma comp_linear_map_injective (f : M₂ →ₗ[R] M) (hf : function.surjective f) :
function.injective (λ g : alternating_map R M N ι, g.comp_linear_map f) :=
λ g₁ g₂ h, ext $ λ x,
by simpa [function.surj_inv_eq hf] using ext_iff.mp h (function.surj_inv hf ∘ x)
lemma comp_linear_map_inj (f : M₂ →ₗ[R] M) (hf : function.surjective f)
(g₁ g₂ : alternating_map R M N ι) : g₁.comp_linear_map f = g₂.comp_linear_map f ↔ g₁ = g₂ :=
(comp_linear_map_injective _ hf).eq_iff
section dom_lcongr
variables (ι R N) (S : Type*) [semiring S] [module S N] [smul_comm_class R S N]
/-- Construct a linear equivalence between maps from a linear equivalence between domains. -/
@[simps apply]
def dom_lcongr (e : M ≃ₗ[R] M₂) : alternating_map R M N ι ≃ₗ[S] alternating_map R M₂ N ι :=
{ to_fun := λ f, f.comp_linear_map e.symm,
inv_fun := λ g, g.comp_linear_map e,
map_add' := λ _ _, rfl,
map_smul' := λ _ _, rfl,
left_inv := λ f, alternating_map.ext $ λ v, f.congr_arg $ funext $ λ i, e.symm_apply_apply _,
right_inv := λ f, alternating_map.ext $ λ v, f.congr_arg $ funext $ λ i, e.apply_symm_apply _ }
@[simp] lemma dom_lcongr_refl :
dom_lcongr R N ι S (linear_equiv.refl R M) = linear_equiv.refl S _ :=
linear_equiv.ext $ λ _, alternating_map.ext $ λ v, rfl
@[simp] lemma dom_lcongr_symm (e : M ≃ₗ[R] M₂) :
(dom_lcongr R N ι S e).symm = dom_lcongr R N ι S e.symm :=
rfl
lemma dom_lcongr_trans (e : M ≃ₗ[R] M₂) (f : M₂ ≃ₗ[R] M₃):
(dom_lcongr R N ι S e).trans (dom_lcongr R N ι S f) = dom_lcongr R N ι S (e.trans f) :=
rfl
end dom_lcongr
/-- Composing an alternating map with the same linear equiv on each argument gives the zero map
if and only if the alternating map is the zero map. -/
@[simp] lemma comp_linear_equiv_eq_zero_iff (f : alternating_map R M N ι) (g : M₂ ≃ₗ[R] M) :
f.comp_linear_map (g : M₂ →ₗ[R] M) = 0 ↔ f = 0 :=
(dom_lcongr R N ι ℕ g.symm).map_eq_zero_iff
variables (f f' : alternating_map R M N ι)
variables (g g₂ : alternating_map R M N' ι)
variables (g' : alternating_map R M' N' ι)
variables (v : ι → M) (v' : ι → M')
open function
/-!
### Other lemmas from `multilinear_map`
-/
section
open_locale big_operators
lemma map_update_sum {α : Type*} (t : finset α) (i : ι) (g : α → M) (m : ι → M):
f (update m i (∑ a in t, g a)) = ∑ a in t, f (update m i (g a)) :=
f.to_multilinear_map.map_update_sum t i g m
end
/-!
### Theorems specific to alternating maps
Various properties of reordered and repeated inputs which follow from
`alternating_map.map_eq_zero_of_eq`.
-/
lemma map_update_self {i j : ι} (hij : i ≠ j) :
f (function.update v i (v j)) = 0 :=
f.map_eq_zero_of_eq _ (by rw [function.update_same, function.update_noteq hij.symm]) hij
lemma map_update_update {i j : ι} (hij : i ≠ j) (m : M) :
f (function.update (function.update v i m) j m) = 0 :=
f.map_eq_zero_of_eq _
(by rw [function.update_same, function.update_noteq hij, function.update_same]) hij
lemma map_swap_add {i j : ι} (hij : i ≠ j) :
f (v ∘ equiv.swap i j) + f v = 0 :=
begin
rw equiv.comp_swap_eq_update,
convert f.map_update_update v hij (v i + v j),
simp [f.map_update_self _ hij,
f.map_update_self _ hij.symm,
function.update_comm hij (v i + v j) (v _) v,
function.update_comm hij.symm (v i) (v i) v],
end
lemma map_add_swap {i j : ι} (hij : i ≠ j) :
f v + f (v ∘ equiv.swap i j) = 0 :=
by { rw add_comm, exact f.map_swap_add v hij }
lemma map_swap {i j : ι} (hij : i ≠ j) : g (v ∘ equiv.swap i j) = - g v :=
eq_neg_of_add_eq_zero_left $ g.map_swap_add v hij
lemma map_perm [fintype ι] (v : ι → M) (σ : equiv.perm ι) :
g (v ∘ σ) = σ.sign • g v :=
begin
apply equiv.perm.swap_induction_on' σ,
{ simp },
{ intros s x y hxy hI,
simpa [g.map_swap (v ∘ s) hxy, equiv.perm.sign_swap hxy] using hI, }
end
lemma map_congr_perm [fintype ι] (σ : equiv.perm ι) :
g v = σ.sign • g (v ∘ σ) :=
by { rw [g.map_perm, smul_smul], simp }
section dom_dom_congr
/-- Transfer the arguments to a map along an equivalence between argument indices.
This is the alternating version of `multilinear_map.dom_dom_congr`. -/
@[simps]
def dom_dom_congr (σ : ι ≃ ι') (f : alternating_map R M N ι) : alternating_map R M N ι' :=
{ to_fun := λ v, f (v ∘ σ),
map_eq_zero_of_eq' := λ v i j hv hij,
f.map_eq_zero_of_eq (v ∘ σ) (by simpa using hv) (σ.symm.injective.ne hij),
.. f.to_multilinear_map.dom_dom_congr σ }
@[simp] lemma dom_dom_congr_refl (f : alternating_map R M N ι) :
f.dom_dom_congr (equiv.refl ι) = f := ext $ λ v, rfl
lemma dom_dom_congr_trans (σ₁ : ι ≃ ι') (σ₂ : ι' ≃ ι'') (f : alternating_map R M N ι) :
f.dom_dom_congr (σ₁.trans σ₂) = (f.dom_dom_congr σ₁).dom_dom_congr σ₂ := rfl
@[simp] lemma dom_dom_congr_zero (σ : ι ≃ ι') :
(0 : alternating_map R M N ι).dom_dom_congr σ = 0 :=
rfl
@[simp] lemma dom_dom_congr_add (σ : ι ≃ ι') (f g : alternating_map R M N ι) :
(f + g).dom_dom_congr σ = f.dom_dom_congr σ + g.dom_dom_congr σ :=
rfl
/-- `alternating_map.dom_dom_congr` as an equivalence.
This is declared separately because it does not work with dot notation. -/
@[simps apply symm_apply]
def dom_dom_congr_equiv (σ : ι ≃ ι') :
alternating_map R M N ι ≃+ alternating_map R M N ι' :=
{ to_fun := dom_dom_congr σ,
inv_fun := dom_dom_congr σ.symm,
left_inv := λ f, by { ext, simp [function.comp] },
right_inv := λ m, by { ext, simp [function.comp] },
map_add' := dom_dom_congr_add σ }
/-- The results of applying `dom_dom_congr` to two maps are equal if and only if those maps are. -/
@[simp] lemma dom_dom_congr_eq_iff (σ : ι ≃ ι') (f g : alternating_map R M N ι) :
f.dom_dom_congr σ = g.dom_dom_congr σ ↔ f = g :=
(dom_dom_congr_equiv σ : _ ≃+ alternating_map R M N ι').apply_eq_iff_eq
@[simp] lemma dom_dom_congr_eq_zero_iff (σ : ι ≃ ι') (f : alternating_map R M N ι) :
f.dom_dom_congr σ = 0 ↔ f = 0 :=
(dom_dom_congr_equiv σ : alternating_map R M N ι ≃+ alternating_map R M N ι').map_eq_zero_iff
lemma dom_dom_congr_perm [fintype ι] (σ : equiv.perm ι) :
g.dom_dom_congr σ = σ.sign • g :=
alternating_map.ext $ λ v, g.map_perm v σ
@[norm_cast] lemma coe_dom_dom_congr (σ : ι ≃ ι') :
↑(f.dom_dom_congr σ) = (f : multilinear_map R (λ _ : ι, M) N).dom_dom_congr σ :=
multilinear_map.ext $ λ v, rfl
end dom_dom_congr
/-- If the arguments are linearly dependent then the result is `0`. -/
lemma map_linear_dependent
{K : Type*} [ring K]
{M : Type*} [add_comm_group M] [module K M]
{N : Type*} [add_comm_group N] [module K N] [no_zero_smul_divisors K N]
(f : alternating_map K M N ι) (v : ι → M)
(h : ¬linear_independent K v) :
f v = 0 :=
begin
obtain ⟨s, g, h, i, hi, hz⟩ := not_linear_independent_iff.mp h,
suffices : f (update v i (g i • v i)) = 0,
{ rw [f.map_smul, function.update_eq_self, smul_eq_zero] at this,
exact or.resolve_left this hz, },
conv at h in (g _ • v _) { rw ←if_t_t (i = x) (g _ • v _), },
rw [finset.sum_ite, finset.filter_eq, finset.filter_ne, if_pos hi, finset.sum_singleton,
add_eq_zero_iff_eq_neg] at h,
rw [h, f.map_neg, f.map_update_sum, neg_eq_zero, finset.sum_eq_zero],
intros j hj,
obtain ⟨hij, _⟩ := finset.mem_erase.mp hj,
rw [f.map_smul, f.map_update_self _ hij.symm, smul_zero],
end
section fin
open fin
/-- A version of `multilinear_map.cons_add` for `alternating_map`. -/
lemma map_vec_cons_add {n : ℕ} (f : alternating_map R M N (fin n.succ)) (m : fin n → M) (x y : M) :
f (matrix.vec_cons (x+y) m) = f (matrix.vec_cons x m) + f (matrix.vec_cons y m) :=
f.to_multilinear_map.cons_add _ _ _
/-- A version of `multilinear_map.cons_smul` for `alternating_map`. -/
lemma map_vec_cons_smul {n : ℕ} (f : alternating_map R M N (fin n.succ)) (m : fin n → M)
(c : R) (x : M) :
f (matrix.vec_cons (c • x) m) = c • f (matrix.vec_cons x m) :=
f.to_multilinear_map.cons_smul _ _ _
end fin
end alternating_map
open_locale big_operators
namespace multilinear_map
open equiv
variables [fintype ι]
private lemma alternization_map_eq_zero_of_eq_aux
(m : multilinear_map R (λ i : ι, M) N')
(v : ι → M) (i j : ι) (i_ne_j : i ≠ j) (hv : v i = v j) :
(∑ (σ : perm ι), σ.sign • m.dom_dom_congr σ) v = 0 :=
begin
rw sum_apply,
exact finset.sum_involution
(λ σ _, swap i j * σ)
(λ σ _, by simp [perm.sign_swap i_ne_j, apply_swap_eq_self hv])
(λ σ _ _, (not_congr swap_mul_eq_iff).mpr i_ne_j)
(λ σ _, finset.mem_univ _)
(λ σ _, swap_mul_involutive i j σ)
end
/-- Produce an `alternating_map` out of a `multilinear_map`, by summing over all argument
permutations. -/
def alternatization : multilinear_map R (λ i : ι, M) N' →+ alternating_map R M N' ι :=
{ to_fun := λ m,
{ to_fun := ⇑(∑ (σ : perm ι), σ.sign • m.dom_dom_congr σ),
map_eq_zero_of_eq' := λ v i j hvij hij, alternization_map_eq_zero_of_eq_aux m v i j hij hvij,
.. (∑ (σ : perm ι), σ.sign • m.dom_dom_congr σ)},
map_add' := λ a b, begin
ext,
simp only [
finset.sum_add_distrib, smul_add, add_apply, dom_dom_congr_apply, alternating_map.add_apply,
alternating_map.coe_mk, smul_apply, sum_apply],
end,
map_zero' := begin
ext,
simp only [
finset.sum_const_zero, smul_zero, zero_apply, dom_dom_congr_apply, alternating_map.zero_apply,
alternating_map.coe_mk, smul_apply, sum_apply],
end }
lemma alternatization_def (m : multilinear_map R (λ i : ι, M) N') :
⇑(alternatization m) = (∑ (σ : perm ι), σ.sign • m.dom_dom_congr σ : _) :=
rfl
lemma alternatization_coe (m : multilinear_map R (λ i : ι, M) N') :
↑m.alternatization = (∑ (σ : perm ι), σ.sign • m.dom_dom_congr σ : _) :=
coe_injective rfl
lemma alternatization_apply (m : multilinear_map R (λ i : ι, M) N') (v : ι → M) :
alternatization m v = ∑ (σ : perm ι), σ.sign • m.dom_dom_congr σ v :=
by simp only [alternatization_def, smul_apply, sum_apply]
end multilinear_map
namespace alternating_map
/-- Alternatizing a multilinear map that is already alternating results in a scale factor of `n!`,
where `n` is the number of inputs. -/
lemma coe_alternatization [fintype ι] (a : alternating_map R M N' ι) :
(↑a : multilinear_map R (λ ι, M) N').alternatization = nat.factorial (fintype.card ι) • a :=
begin
apply alternating_map.coe_injective,
simp_rw [multilinear_map.alternatization_def, ←coe_dom_dom_congr, dom_dom_congr_perm, coe_smul,
smul_smul, int.units_mul_self, one_smul, finset.sum_const, finset.card_univ, fintype.card_perm,
←coe_multilinear_map, coe_smul],
end
end alternating_map
namespace linear_map
variables {N'₂ : Type*} [add_comm_group N'₂] [module R N'₂] [fintype ι]
/-- Composition with a linear map before and after alternatization are equivalent. -/
lemma comp_multilinear_map_alternatization (g : N' →ₗ[R] N'₂)
(f : multilinear_map R (λ _ : ι, M) N') :
(g.comp_multilinear_map f).alternatization = g.comp_alternating_map (f.alternatization) :=
by { ext, simp [multilinear_map.alternatization_def] }
end linear_map
section coprod
open_locale big_operators
open_locale tensor_product
variables {ιa ιb : Type*} [decidable_eq ιa] [decidable_eq ιb] [fintype ιa] [fintype ιb]
variables
{R' : Type*} {Mᵢ N₁ N₂ : Type*}
[comm_semiring R']
[add_comm_group N₁] [module R' N₁]
[add_comm_group N₂] [module R' N₂]
[add_comm_monoid Mᵢ] [module R' Mᵢ]
namespace equiv.perm
/-- Elements which are considered equivalent if they differ only by swaps within α or β -/
abbreviation mod_sum_congr (α β : Type*) :=
_ ⧸ (equiv.perm.sum_congr_hom α β).range
lemma mod_sum_congr.swap_smul_involutive {α β : Type*} [decidable_eq (α ⊕ β)] (i j : α ⊕ β) :
function.involutive (has_smul.smul (equiv.swap i j) : mod_sum_congr α β → mod_sum_congr α β) :=
λ σ, begin
apply σ.induction_on' (λ σ, _),
exact _root_.congr_arg quotient.mk' (equiv.swap_mul_involutive i j σ)
end
end equiv.perm
namespace alternating_map
open equiv
/-- summand used in `alternating_map.dom_coprod` -/
def dom_coprod.summand
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb)
(σ : perm.mod_sum_congr ιa ιb) :
multilinear_map R' (λ _ : ιa ⊕ ιb, Mᵢ) (N₁ ⊗[R'] N₂) :=
quotient.lift_on' σ
(λ σ,
σ.sign •
(multilinear_map.dom_coprod ↑a ↑b : multilinear_map R' (λ _, Mᵢ) (N₁ ⊗ N₂)).dom_dom_congr σ)
(λ σ₁ σ₂ H, begin
rw quotient_group.left_rel_apply at H,
obtain ⟨⟨sl, sr⟩, h⟩ := H,
ext v,
simp only [multilinear_map.dom_dom_congr_apply, multilinear_map.dom_coprod_apply,
coe_multilinear_map, multilinear_map.smul_apply],
replace h := inv_mul_eq_iff_eq_mul.mp (h.symm),
have : (σ₁ * perm.sum_congr_hom _ _ (sl, sr)).sign = σ₁.sign * (sl.sign * sr.sign) :=
by simp,
rw [h, this, mul_smul, mul_smul, smul_left_cancel_iff,
←tensor_product.tmul_smul, tensor_product.smul_tmul'],
simp only [sum.map_inr, perm.sum_congr_hom_apply, perm.sum_congr_apply, sum.map_inl,
function.comp_app, perm.coe_mul],
rw [←a.map_congr_perm (λ i, v (σ₁ _)), ←b.map_congr_perm (λ i, v (σ₁ _))],
end)
lemma dom_coprod.summand_mk'
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb)
(σ : equiv.perm (ιa ⊕ ιb)) :
dom_coprod.summand a b (quotient.mk' σ) = σ.sign •
(multilinear_map.dom_coprod ↑a ↑b : multilinear_map R' (λ _, Mᵢ) (N₁ ⊗ N₂)).dom_dom_congr σ :=
rfl
/-- Swapping elements in `σ` with equal values in `v` results in an addition that cancels -/
lemma dom_coprod.summand_add_swap_smul_eq_zero
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb)
(σ : perm.mod_sum_congr ιa ιb)
{v : ιa ⊕ ιb → Mᵢ} {i j : ιa ⊕ ιb} (hv : v i = v j) (hij : i ≠ j) :
dom_coprod.summand a b σ v + dom_coprod.summand a b (swap i j • σ) v = 0 :=
begin
apply σ.induction_on' (λ σ, _),
dsimp only [quotient.lift_on'_mk', quotient.map'_mk', mul_action.quotient.smul_mk,
dom_coprod.summand],
rw [smul_eq_mul, perm.sign_mul, perm.sign_swap hij],
simp only [one_mul, neg_mul, function.comp_app, units.neg_smul, perm.coe_mul,
units.coe_neg, multilinear_map.smul_apply, multilinear_map.neg_apply,
multilinear_map.dom_dom_congr_apply, multilinear_map.dom_coprod_apply],
convert add_right_neg _;
{ ext k, rw equiv.apply_swap_eq_self hv },
end
/-- Swapping elements in `σ` with equal values in `v` result in zero if the swap has no effect
on the quotient. -/
lemma dom_coprod.summand_eq_zero_of_smul_invariant
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb)
(σ : perm.mod_sum_congr ιa ιb)
{v : ιa ⊕ ιb → Mᵢ} {i j : ιa ⊕ ιb} (hv : v i = v j) (hij : i ≠ j) :
swap i j • σ = σ → dom_coprod.summand a b σ v = 0 :=
begin
apply σ.induction_on' (λ σ, _),
dsimp only [quotient.lift_on'_mk', quotient.map'_mk', multilinear_map.smul_apply,
multilinear_map.dom_dom_congr_apply, multilinear_map.dom_coprod_apply, dom_coprod.summand],
intro hσ,
with_cases
{ cases hi : σ⁻¹ i;
cases hj : σ⁻¹ j;
rw perm.inv_eq_iff_eq at hi hj;
substs hi hj, },
case [sum.inl sum.inr : i' j', sum.inr sum.inl : i' j']
{ -- the term pairs with and cancels another term
all_goals { obtain ⟨⟨sl, sr⟩, hσ⟩ := quotient_group.left_rel_apply.mp (quotient.exact' hσ), },
work_on_goal 1 { replace hσ := equiv.congr_fun hσ (sum.inl i'), },
work_on_goal 2 { replace hσ := equiv.congr_fun hσ (sum.inr i'), },
all_goals
{ rw [smul_eq_mul, ←mul_swap_eq_swap_mul, mul_inv_rev, swap_inv, inv_mul_cancel_right] at hσ,
simpa using hσ, }, },
case [sum.inr sum.inr : i' j', sum.inl sum.inl : i' j']
{ -- the term does not pair but is zero
all_goals { convert smul_zero _, },
work_on_goal 1 { convert tensor_product.tmul_zero _ _, },
work_on_goal 2 { convert tensor_product.zero_tmul _ _, },
all_goals { exact alternating_map.map_eq_zero_of_eq _ _ hv (λ hij', hij (hij' ▸ rfl)), } },
end
/-- Like `multilinear_map.dom_coprod`, but ensures the result is also alternating.
Note that this is usually defined (for instance, as used in Proposition 22.24 in [Gallier2011Notes])
over integer indices `ιa = fin n` and `ιb = fin m`, as
$$
(f \wedge g)(u_1, \ldots, u_{m+n}) =
\sum_{\operatorname{shuffle}(m, n)} \operatorname{sign}(\sigma)
f(u_{\sigma(1)}, \ldots, u_{\sigma(m)}) g(u_{\sigma(m+1)}, \ldots, u_{\sigma(m+n)}),
$$
where $\operatorname{shuffle}(m, n)$ consists of all permutations of $[1, m+n]$ such that
$\sigma(1) < \cdots < \sigma(m)$ and $\sigma(m+1) < \cdots < \sigma(m+n)$.
Here, we generalize this by replacing:
* the product in the sum with a tensor product
* the filtering of $[1, m+n]$ to shuffles with an isomorphic quotient
* the additions in the subscripts of $\sigma$ with an index of type `sum`
The specialized version can be obtained by combining this definition with `fin_sum_fin_equiv` and
`linear_map.mul'`.
-/
@[simps]
def dom_coprod
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb) :
alternating_map R' Mᵢ (N₁ ⊗[R'] N₂) (ιa ⊕ ιb) :=
{ to_fun := λ v, ⇑(∑ σ : perm.mod_sum_congr ιa ιb, dom_coprod.summand a b σ) v,
map_eq_zero_of_eq' := λ v i j hv hij, begin
dsimp only,
rw multilinear_map.sum_apply,
exact finset.sum_involution
(λ σ _, equiv.swap i j • σ)
(λ σ _, dom_coprod.summand_add_swap_smul_eq_zero a b σ hv hij)
(λ σ _, mt $ dom_coprod.summand_eq_zero_of_smul_invariant a b σ hv hij)
(λ σ _, finset.mem_univ _)
(λ σ _, equiv.perm.mod_sum_congr.swap_smul_involutive i j σ),
end,
..(∑ σ : perm.mod_sum_congr ιa ιb, dom_coprod.summand a b σ) }
lemma dom_coprod_coe (a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb) :
(↑(a.dom_coprod b) : multilinear_map R' (λ _, Mᵢ) _) =
∑ σ : perm.mod_sum_congr ιa ιb, dom_coprod.summand a b σ :=
multilinear_map.ext $ λ _, rfl
/-- A more bundled version of `alternating_map.dom_coprod` that maps
`((ι₁ → N) → N₁) ⊗ ((ι₂ → N) → N₂)` to `(ι₁ ⊕ ι₂ → N) → N₁ ⊗ N₂`. -/
def dom_coprod' :
(alternating_map R' Mᵢ N₁ ιa ⊗[R'] alternating_map R' Mᵢ N₂ ιb) →ₗ[R']
alternating_map R' Mᵢ (N₁ ⊗[R'] N₂) (ιa ⊕ ιb) :=
tensor_product.lift $ by
refine linear_map.mk₂ R' (dom_coprod)
(λ m₁ m₂ n, _)
(λ c m n, _)
(λ m n₁ n₂, _)
(λ c m n, _);
{ ext,
simp only [dom_coprod_apply, add_apply, smul_apply, ←finset.sum_add_distrib,
finset.smul_sum, multilinear_map.sum_apply, dom_coprod.summand],
congr,
ext σ,
apply σ.induction_on' (λ σ, _),
simp only [quotient.lift_on'_mk', coe_add, coe_smul, multilinear_map.smul_apply,
←multilinear_map.dom_coprod'_apply],
simp only [tensor_product.add_tmul, ←tensor_product.smul_tmul',
tensor_product.tmul_add, tensor_product.tmul_smul, linear_map.map_add, linear_map.map_smul],
rw ←smul_add <|> rw smul_comm,
congr }
@[simp]
lemma dom_coprod'_apply
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb) :
dom_coprod' (a ⊗ₜ[R'] b) = dom_coprod a b :=
by simp only [dom_coprod', tensor_product.lift.tmul, linear_map.mk₂_apply]
end alternating_map
open equiv
/-- A helper lemma for `multilinear_map.dom_coprod_alternization`. -/
lemma multilinear_map.dom_coprod_alternization_coe
(a : multilinear_map R' (λ _ : ιa, Mᵢ) N₁) (b : multilinear_map R' (λ _ : ιb, Mᵢ) N₂) :
multilinear_map.dom_coprod ↑a.alternatization ↑b.alternatization =
∑ (σa : perm ιa) (σb : perm ιb), σa.sign • σb.sign •
multilinear_map.dom_coprod (a.dom_dom_congr σa) (b.dom_dom_congr σb) :=
begin
simp_rw [←multilinear_map.dom_coprod'_apply, multilinear_map.alternatization_coe],
simp_rw [tensor_product.sum_tmul, tensor_product.tmul_sum, linear_map.map_sum,
←tensor_product.smul_tmul', tensor_product.tmul_smul, linear_map.map_smul_of_tower],
end
open alternating_map
/-- Computing the `multilinear_map.alternatization` of the `multilinear_map.dom_coprod` is the same
as computing the `alternating_map.dom_coprod` of the `multilinear_map.alternatization`s.
-/
lemma multilinear_map.dom_coprod_alternization
(a : multilinear_map R' (λ _ : ιa, Mᵢ) N₁) (b : multilinear_map R' (λ _ : ιb, Mᵢ) N₂) :
(multilinear_map.dom_coprod a b).alternatization =
a.alternatization.dom_coprod b.alternatization :=
begin
apply coe_multilinear_map_injective,
rw [dom_coprod_coe, multilinear_map.alternatization_coe,
finset.sum_partition (quotient_group.left_rel (perm.sum_congr_hom ιa ιb).range)],
congr' 1,
ext1 σ,
apply σ.induction_on' (λ σ, _),
-- unfold the quotient mess left by `finset.sum_partition`
conv in (_ = quotient.mk' _)
{ change quotient.mk' _ = quotient.mk' _,
rw quotient_group.eq' },
-- eliminate a multiplication
have : @finset.univ (perm (ιa ⊕ ιb)) _ = finset.univ.image ((*) σ) :=
(finset.eq_univ_iff_forall.mpr $ λ a, let ⟨a', ha'⟩ := mul_left_surjective σ a in
finset.mem_image.mpr ⟨a', finset.mem_univ _, ha'⟩).symm,
rw [this, finset.image_filter],
simp only [function.comp, mul_inv_rev, inv_mul_cancel_right, subgroup.inv_mem_iff],
simp only [monoid_hom.mem_range], -- needs to be separate from the above `simp only`
rw [finset.filter_congr_decidable,
finset.univ_filter_exists (perm.sum_congr_hom ιa ιb),
finset.sum_image (λ x _ y _ (h : _ = _), mul_right_injective _ h),
finset.sum_image (λ x _ y _ (h : _ = _), perm.sum_congr_hom_injective h)],
dsimp only,
-- now we're ready to clean up the RHS, pulling out the summation
rw [dom_coprod.summand_mk', multilinear_map.dom_coprod_alternization_coe,
←finset.sum_product', finset.univ_product_univ,
←multilinear_map.dom_dom_congr_equiv_apply, add_equiv.map_sum, finset.smul_sum],
congr' 1,
ext1 ⟨al, ar⟩,
dsimp only,
-- pull out the pair of smuls on the RHS, by rewriting to `_ →ₗ[ℤ] _` and back
rw [←add_equiv.coe_to_add_monoid_hom, ←add_monoid_hom.coe_to_int_linear_map,
linear_map.map_smul_of_tower,
linear_map.map_smul_of_tower,
add_monoid_hom.coe_to_int_linear_map, add_equiv.coe_to_add_monoid_hom,
multilinear_map.dom_dom_congr_equiv_apply],
-- pick up the pieces
rw [multilinear_map.dom_dom_congr_mul, perm.sign_mul,
perm.sum_congr_hom_apply, multilinear_map.dom_coprod_dom_dom_congr_sum_congr,
perm.sign_sum_congr, mul_smul, mul_smul],
end
/-- Taking the `multilinear_map.alternatization` of the `multilinear_map.dom_coprod` of two
`alternating_map`s gives a scaled version of the `alternating_map.coprod` of those maps.
-/
lemma multilinear_map.dom_coprod_alternization_eq
(a : alternating_map R' Mᵢ N₁ ιa) (b : alternating_map R' Mᵢ N₂ ιb) :
(multilinear_map.dom_coprod a b : multilinear_map R' (λ _ : ιa ⊕ ιb, Mᵢ) (N₁ ⊗ N₂))
.alternatization =
((fintype.card ιa).factorial * (fintype.card ιb).factorial) • a.dom_coprod b :=
begin
rw [multilinear_map.dom_coprod_alternization, coe_alternatization, coe_alternatization, mul_smul,
←dom_coprod'_apply, ←dom_coprod'_apply, ←tensor_product.smul_tmul', tensor_product.tmul_smul,
linear_map.map_smul_of_tower dom_coprod', linear_map.map_smul_of_tower dom_coprod'],
-- typeclass resolution is a little confused here
apply_instance, apply_instance,
end
end coprod
section basis
open alternating_map
variables {ι₁ : Type*} [fintype ι]
variables {R' : Type*} {N₁ N₂ : Type*} [comm_semiring R'] [add_comm_monoid N₁] [add_comm_monoid N₂]
variables [module R' N₁] [module R' N₂]
/-- Two alternating maps indexed by a `fintype` are equal if they are equal when all arguments
are distinct basis vectors. -/
lemma basis.ext_alternating {f g : alternating_map R' N₁ N₂ ι} (e : basis ι₁ R' N₁)
(h : ∀ v : ι → ι₁, function.injective v → f (λ i, e (v i)) = g (λ i, e (v i))) : f = g :=
begin
refine alternating_map.coe_multilinear_map_injective (basis.ext_multilinear e $ λ v, _),
by_cases hi : function.injective v,
{ exact h v hi },
{ have : ¬function.injective (λ i, e (v i)) := hi.imp function.injective.of_comp,
rw [coe_multilinear_map, coe_multilinear_map,
f.map_eq_zero_of_not_injective _ this, g.map_eq_zero_of_not_injective _ this], }
end
end basis
/-! ### Currying -/
section currying
variables
{R' : Type*} {M'' M₂'' N'' N₂'': Type*}
[comm_semiring R']
[add_comm_monoid M''] [add_comm_monoid M₂''] [add_comm_monoid N''] [add_comm_monoid N₂'']
[module R' M''] [module R' M₂''] [module R' N''] [module R' N₂'']
namespace alternating_map
/-- Given an alternating map `f` in `n+1` variables, split the first variable to obtain
a linear map into alternating maps in `n` variables, given by `x ↦ (m ↦ f (matrix.vec_cons x m))`.
It can be thought of as a map $Hom(\bigwedge^{n+1} M, N) \to Hom(M, Hom(\bigwedge^n M, N))$.
This is `multilinear_map.curry_left` for `alternating_map`. See also
`alternating_map.curry_left_linear_map`. -/
@[simps]
def curry_left {n : ℕ} (f : alternating_map R' M'' N'' (fin n.succ)) :
M'' →ₗ[R'] alternating_map R' M'' N'' (fin n) :=
{ to_fun := λ m,
{ to_fun := λ v, f (matrix.vec_cons m v),
map_eq_zero_of_eq' := λ v i j hv hij, f.map_eq_zero_of_eq _
(by rwa [matrix.cons_val_succ, matrix.cons_val_succ]) ((fin.succ_injective _).ne hij),
.. f.to_multilinear_map.curry_left m },
map_add' := λ m₁ m₂, ext $ λ v, f.map_vec_cons_add _ _ _,
map_smul' := λ r m, ext $ λ v, f.map_vec_cons_smul _ _ _ }
@[simp] lemma curry_left_zero {n : ℕ} :
curry_left (0 : alternating_map R' M'' N'' (fin n.succ)) = 0 := rfl
@[simp] lemma curry_left_add {n : ℕ} (f g : alternating_map R' M'' N'' (fin n.succ)) :
curry_left (f + g) = curry_left f + curry_left g := rfl
@[simp] lemma curry_left_smul {n : ℕ} (r : R') (f : alternating_map R' M'' N'' (fin n.succ)) :
curry_left (r • f) = r • curry_left f := rfl
/-- `alternating_map.curry_left` as a `linear_map`. This is a separate definition as dot notation
does not work for this version. -/
@[simps]
def curry_left_linear_map {n : ℕ} :
alternating_map R' M'' N'' (fin n.succ) →ₗ[R'] M'' →ₗ[R'] alternating_map R' M'' N'' (fin n) :=
{ to_fun := λ f, f.curry_left,
map_add' := curry_left_add,
map_smul' := curry_left_smul }
/-- Currying with the same element twice gives the zero map. -/
@[simp] lemma curry_left_same {n : ℕ} (f : alternating_map R' M'' N'' (fin n.succ.succ)) (m : M'') :
(f.curry_left m).curry_left m = 0 :=
ext $ λ x, f.map_eq_zero_of_eq _ (by simp) fin.zero_ne_one
@[simp] lemma curry_left_comp_alternating_map {n : ℕ} (g : N'' →ₗ[R'] N₂'')
(f : alternating_map R' M'' N'' (fin n.succ)) (m : M'') :
(g.comp_alternating_map f).curry_left m = g.comp_alternating_map (f.curry_left m) :=
rfl
@[simp] lemma curry_left_comp_linear_map {n : ℕ} (g : M₂'' →ₗ[R'] M'')
(f : alternating_map R' M'' N'' (fin n.succ)) (m : M₂'') :
(f.comp_linear_map g).curry_left m = (f.curry_left (g m)).comp_linear_map g :=
ext $ λ v, congr_arg f $ funext $ begin
refine fin.cases _ _,
{ refl },
{ simp }
end
/-- The space of constant maps is equivalent to the space of maps that are alternating with respect
to an empty family. -/
@[simps] def const_linear_equiv_of_is_empty [is_empty ι] :
N'' ≃ₗ[R'] alternating_map R' M'' N'' ι :=
{ to_fun := alternating_map.const_of_is_empty R' M'',
map_add' := λ x y, rfl,
map_smul' := λ t x, rfl,
inv_fun := λ f, f 0,
left_inv := λ _, rfl,
right_inv := λ f, ext $ λ x, alternating_map.congr_arg f $ subsingleton.elim _ _ }
end alternating_map
end currying
|